Trajectoires d’usage dans l’accueil temps libre chez les enfants de 3 à 12 ans en Belgique francophone - Martin Wagener; Carole Bonnetier; Florence Degavre (Recherches Sociologiques et Anthropologiques)
The significant diversity of the out-of-school care (ATL – accueil temps libre) landscape in French-speaking Belgium raises important questions about accessibility. This article analyzes how families use ATL activities subsidized by the Office for Birth and Childhood (ONE), drawing on a multidimensional conception of accessibility and ODENORE’s1 work on non-take-up of public services. Interviews with professionals and parents reveal usage trajectories that highlight the dynamic and relational nature of non-take-up, as well as families’ relationships with leisure institutions – closely tied to their class ethos. The typology developed is discussed in light of the research by Liénard and Servais.